Fostering Innovation in Chile - Benavente, José-Miguel (OECD Publishing, 2005)
A good framework for investment in innovation can contribute to increasing Chile's growth potential. Spending on R&D is currently low in relation to GDP and heavily reliant on government financing. Innovation activity in the business sector is also limited by insufficient seed and venture capital and human capital constraints. This is despite several favourable framework conditions, including a stable macro-economy, liberal foreign trade and investment regimes, and reasonably pro-competition regulations in product markets. The government intends to increase public spending on R&D, to be financed by revenue from the mining tax introduced in May 2005, and to create a National Innovation Council. The effectiveness of these measures will depend largely on the extent to which they will boost business-financed innovation consistent with Chile's comparative advantages. This Working Paper relates to the 2005 OECD Economic Survey of Chile (www.oecd.org/eco/surveys/chile)
Keywords: Economics; Chile